The Secret Textual History of Pamela, Methodist - Winckles, Andrew (Mémoires du livre / Studies in Book Culture, 2015)
This essay will trace how the closely linked discursive practices of oral testimony in Methodist classes and bands, manuscript circulation via letter of spiritual experience accounts, and publication of letters and narratives in the Arminian Magazine can be mapped onto the discourse culture that brought about the publication of Samuel Richardson’s Pamela and the resultant media storm that was only rivalled by the vehemence of the attacks on Methodism in the contemporary press. This history makes clear some of the links between the discourse of evangelicalism and the discourse of the early novel, most notably in the shared textual histories and similar protocols of mediation that define early works in each field.